Kinerja Bus Trans Batam Koridor I (Sekupang – Batam Center) - Monica Kusuma Dita; Adhitomo Wirawan (Institut Transportasi dan Logistik Trisakti, 2020)
This study aims to analyze the performance of Batam BRT (Bus Rapid Transit) Corridor I (Sekupang - Batam Center). The average waiting time, the average travel time of bus stop from one to the other, the average number of passengers during working hours and the average total time travel were analyzed. This study is an evaluative research. The data used in this study is primary data taken from an observation and interview. The population of the study was Batam BRT Corridor I Sekupang-Batam Center with one driver as the sample. The standard used to evaluate the performance of Batam BRT is the World Bank public transport performance standard. The result of the study shows that the performance of Batam BRT does not meet the World Bank public transport performance standard.